Prediksi Persediaan Obat Pada Apotek Menggunakan Algoritma Decision Tree - Pratiwi, Sinta Amanda; Fauzi, Ahmad; Puspita Lestari, Santi Arum; Cahyana, Yana (STMIK Budi Darma, 2024)
A pharmacy is a place for buying and selling drugs and must have an adequate stock of drug supplies so that it can serve consumers in need. In some pharmacies there are problems related to drug supply. Often the drugs needed by the community are empty in stock, while the drugs that are less needed are stored in the warehouse. Therefore, this study aims to conduct a prediction model of drug supply so that it can meet consumer needs. This study uses drug inventory data at Kaligandu Pharmacy, the data has 2745 rows and 5 attributes consisting of